2024
DOI: 10.1088/1361-6501/ad2052
|View full text |Cite
|
Sign up to set email alerts
|

Transfer learning rolling bearing fault diagnosis model based on deep feature decomposition and class-level alignment

Jingchuan Dong,
Hongyu Jiang,
Depeng Su
et al.

Abstract: Research on transfer learning in rolling bearing fault diagnosis can help overcome challenges such as different data distributions and limited fault samples. However, most existing methods still struggle to address the zero-shot cross-domain problem within the same equipment and the few-shot cross-machine problem. In response to these challenges, this paper introduces a transfer learning rolling bearing fault diagnosis model based on deep feature decomposition and class-level alignment (FDCATL). The model cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Attention mechanisms have revolutionized the way neural networks process information by enabling models to focus on specific parts of the input data, improving efficiency and performance across tasks such as classification, prediction and beyond UrRehman et al (2024). In recent years, an increasing number of empirical studies have demonstrated the significant role of incorporating attention mechanisms into bearing fault diagnosis Yao et al (2023), Dong et al (2024), Han et al (2024). This approach allows the model to selectively focus on key data points, thereby enhancing its ability to identify important fault characteristics with greater accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…Attention mechanisms have revolutionized the way neural networks process information by enabling models to focus on specific parts of the input data, improving efficiency and performance across tasks such as classification, prediction and beyond UrRehman et al (2024). In recent years, an increasing number of empirical studies have demonstrated the significant role of incorporating attention mechanisms into bearing fault diagnosis Yao et al (2023), Dong et al (2024), Han et al (2024). This approach allows the model to selectively focus on key data points, thereby enhancing its ability to identify important fault characteristics with greater accuracy.…”
Section: Introductionmentioning
confidence: 99%